2012
DOI: 10.1001/archgenpsychiatry.2012.271
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Outcome of Childhood Attention-Deficit/Hyperactivity Disorder 33 Years Later

Abstract: Context Prospective studies of childhood attention deficit/hyperactivity disorder (ADHD) have not extended beyond early adulthood. Objective To test whether children diagnosed with ADHD at mean age 8 (probands) have worse educational, occupational, economic, social, marital outcomes; higher rates of ongoing ADHD, antisocial personality disorder (ASPD), substance disorders (SD); adult onset psychiatric disorders, psychiatric hospitalizations and incarcerations, than non-ADHD comparisons, at mean age 41. To te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
429
6
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 530 publications
(478 citation statements)
references
References 39 publications
(42 reference statements)
28
429
6
15
Order By: Relevance
“…The authors noted that the exclusion of children with primary aggression or other antisocial behavior might have resulted in a baseline sample with low overall impairment, with consequently improved adult outcomes. In the 33-year follow up (mean age = 41), the authors reported a 22.2% prevalence of ADHD in probands, who also showed poorer educational and occupational outcomes than comparisons, as well as higher rates of divorce, incarceration, and death (Klein et al, 2012). Probands did not differ from comparisons, though, in rates of mood or anxiety disorders or adult-onset psychopathology.…”
Section: Prospective Investigations In Malesmentioning
confidence: 92%
“…The authors noted that the exclusion of children with primary aggression or other antisocial behavior might have resulted in a baseline sample with low overall impairment, with consequently improved adult outcomes. In the 33-year follow up (mean age = 41), the authors reported a 22.2% prevalence of ADHD in probands, who also showed poorer educational and occupational outcomes than comparisons, as well as higher rates of divorce, incarceration, and death (Klein et al, 2012). Probands did not differ from comparisons, though, in rates of mood or anxiety disorders or adult-onset psychopathology.…”
Section: Prospective Investigations In Malesmentioning
confidence: 92%
“…Aggression is a well‐established adverse, potentially harmful outcome in individuals with ADHD (Klein et al., 2012; Thapar, Langley, Owen, & O'Donovan, 2007). It also indexes an important ADHD clinical subtype characterised by greater clinical severity and poorer prognosis even after treatment (Klein et al., 2012; Thapar et al., 2007) .…”
Section: Introductionmentioning
confidence: 99%
“…It also indexes an important ADHD clinical subtype characterised by greater clinical severity and poorer prognosis even after treatment (Klein et al., 2012; Thapar et al., 2007) . Thus, it is a priority to identify novel psychological and biological targets for informing the future development of effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made in the acceptance of ADHD in children, however, despite European wide consensus validating ADHD as a condition persisting into adulthood [13], it remains under-diagnosed and under-treated in adults [14]. Having ADHD as an adult can have significant implications for education, work, independent daily living, and social relationships [15]. The consequences of not diagnosing and treating ADHD in adults appropriately can also result in high rates of substance misuse or offending, with broader implications for health and social care, and wider society as a whole [14].…”
Section: B Adult Adhd and Stigmamentioning
confidence: 99%